Inovasi AIoT (Artificial Intellegence Internet of Things) untuk Penyiraman Otomatis di RPTRA Abdi Praja - Ariawan, Angga; Hendra, Anderson (PUAN INDONESIA, 2024)
The Abdi Praja RPTRA is a green open space that faces challenges in inefficient watering of plants. This Community Service Program (PkM) aims to overcome this problem by implementing an automatic watering system based on artificial intelligence (AI) and the Internet of Things (IoT). This program aims to improve water use efficiency, plant health and environmental quality as well as supporting reforestation and sustainability of green spaces. Media Nusantara Citra University students will be actively involved in the development and application of this technology, as well as providing education to the public about environmentally friendly technology. This automatic watering system is adjusted to weather conditions and air humidity which will be processed using the Fuzzy Logic algorithm as real-time artificial intelligence, so it can save water and ensure optimal care for plants.